2016
DOI: 10.1007/s11517-016-1496-7
|View full text |Cite
|
Sign up to set email alerts
|

A method to qualitatively assess arm use in stroke survivors in the home environment

Abstract: Wearable sensor technology has enabled unobtrusive monitoring of arm movements of stroke survivors in the home environment. However, the most widely established method, based on activity counts, provides quantitative rather than qualitative information on arm without functional insights, and is sensitive to passive arm movements during ambulatory activities. We propose a method to quantify functionally relevant arm use in stroke survivors relying on a single wrist-worn inertial measurement unit. Orientation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 35 publications
1
99
0
1
Order By: Relevance
“…Only features from the time domain were taken for further analysis as we have shown that in “real world” applications, frequency domain features usually do not provide useful information ( 40 ). In addition, some high level features were included: AC ( 41 ), total distance traveled and distance traveled actively ( 40 ), altitude difference within one epoch, altitude variance within one epoch, and time above acceleration magnitude threshold (empirically chosen). In order to test whether the inclusion of HR improves the overall accuracy of EE estimation, as shown by Nightingale et al ( 42 ), mean HR, resting HR and the difference between mean HR and resting HR were included as additional features.…”
Section: Methodsmentioning
confidence: 99%
“…Only features from the time domain were taken for further analysis as we have shown that in “real world” applications, frequency domain features usually do not provide useful information ( 40 ). In addition, some high level features were included: AC ( 41 ), total distance traveled and distance traveled actively ( 40 ), altitude difference within one epoch, altitude variance within one epoch, and time above acceleration magnitude threshold (empirically chosen). In order to test whether the inclusion of HR improves the overall accuracy of EE estimation, as shown by Nightingale et al ( 42 ), mean HR, resting HR and the difference between mean HR and resting HR were included as additional features.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the presence of the therapist could influence the patient performance during the measurement. A reduced sensor set would improve the problem of obtrusiveness (Leuenberger et al, 2016 ; van Meulen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In stroke clinical trials, acceleration sensors have been used to measure the patient arm-activities in real world (Uswatte et al, 2005 ). Although accelerometer sensors can be used to measure movements in the sagittal plane (Leuenberger et al, 2016 ), they cannot provide information regarding three-dimensional (3D) movements of the upper limb. To measure movement quality kinematic metrics from optical motion capture systems quantify the patients’ motor abilities on a body function level but remain restricted to a motion capture laboratory and cannot be used in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…For activity tracking, a single 6 DOF IMU sensor with complex feature extraction and motion separation algorithms are necessary to detect different movements and identify activities. More complex motion tracking, such as detection of limb and body part movements and posture is possible through securing multiple IMUs with important clinical applications from lower back pain [ 48 ] to stroke rehabilitation [ 49 ] and gait monitoring [ 50 ]. For example, Hajibozorgi et al [ 48 ] have used multiple IMUs placed on the back to monitor posture and range of motion (ROM) of spine.…”
Section: Activity Posture and Muscle Movement Monitoringmentioning
confidence: 99%